Pozzolanic Reactivity of Pulverized Ceramic Waste as Partial Substitute for Cement and Supplementary Cementitious Materials in Concrete - M. O. Ajadi (Journal of Applied Sciences and Environmental Management)
The pozzolanic reactivity of the adhesive stabiliser enhances the performance of supplementary cementitious materials (SCMs) in mortar compositions, and alternative ways of reducing carbonic emission of cement (CO2) have been a global concern. Hence, the objective of this paper is to investigate the pozzolanic reactivity of pulverised ceramic waste (CW) as partial substitution for cement and supplementary cementitious materials in concrete making using appropriate standard methods after water-cured for 7, 14, and 28 days. From resilient test, the compressive strength of bricks with sole cement has a higher resistance 1.55, 1.59 and 1.64MPa of 7, 14, and 28 water cured days, respectively. The study unveiled characterisation of CW’s properties as a potential recycling material for cementitious compositions with its partial replacement for cement at (CW01-05% to CM09-05% of 10%) and its equal substitution for SCMs at (CW30%/GD30%/RS30% of 90%). The results revealed strength of 1.18, 1.24, 1.34, 1.41 and 1.49MPa, respectively for the mixtures at water curing for 7 days, 1.24, 1.29, 1.36, 1.44, 1.52MPa at water curing for 14 days, and 28 days of water curing has the highest strength of 1.26, 1.32, 1.39, 1.52, 1.60Mpa. In conclusion, CW has a substantial influence on compressive strength of cementitious bricks and can serve as a partial substitute for cement compositions.